What Happens after Kasai for Biliary Atresia? A European Multicenter Survey - Wong, Zeng Hao; Davenport, Mark (European Journal of Pediatric Surgery, 2019)
Aim Biliary atresia (BA) remains a rare disease in Europe with an estimated incidence of 1 in 15–20,000 livebirths. While the Kasai portoenterostomy (KPE) is regarded as the standard operation for BA, there is no consensus on optimum adjuvant therapy. We sought to determine the variation in therapy and opinion in centers known to have an interest in pediatric hepatobiliary surgery across Europe.Methods A survey of current pre- and postoperative practice was circulated to surgeons and centers known to have an interest in BA. Data are quoted as median (range).Results There were 19 completed center forms from 12 different countries. Annual (new) caseload varied with 10 centers reported seeing ≤5 patients/year and 4 centers >15 patients/year. The distribution of BA variants was isolated BA (80 [60–100]%), syndromic BA (10 [3–35]%), cystic BA (5 [1–15]%), and cytomegalovirus (CMV) immunoglobulin M (IgM)-positive BA (5 [0–15]% (CMV serology only formally tested in 16 centers). The commonest age group at KPE was 51 to 60 days (n = 8). All centers performed an exclusively open KPE, although one used laparoscopy for diagnosis. A steroid-based postoperative regimen was used in 11/19 (58%) centers, but with marked variation in dose and duration. Commonest perioperative antibiotics were a combination of piperacillin-tazocin (n = 7) and gentamicin (n = 8). Oral prophylactic antibiotics, with varying duration (4–52 weeks) were used in 13/19 (68%) centers. If CMV serology was positive, seven centers would treat with specific antiviral therapy. Other postoperative medication included ursodeoxycholic acid (UDCA) (n = 19), phenobarbitone (n = 4), and cholestyramine (n = 2). Self-declared clearance of jaundice in centers varied from 30 to 40% (n = 3) to > 60% (n = 5).Conclusion All surveyed European centers continue to perform an exclusively open KPE, but there is no consensus on a standard adjuvant drug regimen. Self-declared outcome post-KPE also appears to be variable though the reasons are obscure.
Keywords: biliary atresia; adjuvant therapy; Kasai portoenterostomy; corticosteroids; ursodeoxycholic acid